Formation, Optical Properties and Applications of Edge Gold-Coated Silver Nanoprisms. Issue 1737 (9th June 2015) - Shahjamali, Mohammad M.; Salvador, Michael; Zaraee, Negin
ABSTRACT: A facile, high-yield synthesis of edge gold-coated silver nanoprisms (GSNPs) with a gold nanoframe as thin as 1.7 nm and their comprehensive characterizations by using various spectroscopic and microscopic techniques is introduced. The GSNPs exhibit remarkably higher stability than silver nanoprisms (SNPs) and are therefore explored as effective optical antennae for light-harvesting applications. When embedded into a bulk heterojunctions film of P3HT:PCBM, plasmonic GSNPs with a localized surface plasmon resonance (LSPR) around 500 nm can effectively act as optical antennae to enhance light harvesting in the active layer. As a result, we measured up to 7-fold enhancement in the polaron generation yield through photoinduced absorption spectroscopy. Owing to the high stability and strong field enhancement, the presented GSNPs feature great potential as plasmonic probes for photovoltaic applications and LSPR sensing.